1961
DOI: 10.1021/jo01065a605
|View full text |Cite
|
Sign up to set email alerts
|

Notes- Preparation of Methyl β-Hydroxybutyrate from Propylene Oxide, Carbon Monoxide, Methanol, and Dicobalt Octacarbonyl.

Abstract: Behavior of the lactone of cis-S-hydroxycyclohexanecarboxylic acid in concentrated sulfuric add. Fifteen grams of the lactone of cis-3-hydroxycyclohexanecarboxylic acid was dissolved in 50 ml. of coned, sulfuric acid and allowed to stand at room temperature for 48 hr. At the end of this period the opaque brown mixture was poured into water and continuously extracted with ether. The extracts were dried, evaporated, and the product fractionally distilled. The main fraction, b.p. 115°( 8 mm.) weighing 4.2 g. (28%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1964
1964
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 2 publications
(2 reference statements)
0
27
0
Order By: Relevance
“…[347] For example, early studies by Heck demonstrated that sodium tetracarbonylcobaltate catalyzes a facile carbonylative ring opening of epoxides to generate either a polyester such as 314 or a bhydroxy ester such as 315 in good yield (Scheme 104). [348] A 1994 patent reported the dramatic rate enhancement of the [Co 2 (CO) 8 ]-catalyzed carbonylation in the presence of 3-hydroxypyridine (Scheme 105). [349] Careful control of the reaction conditions can allow for the formation of the blactone or polymerization to form polyesters.…”
Section: Lewis Base Catalysis With Cobaltmentioning
confidence: 99%
“…[347] For example, early studies by Heck demonstrated that sodium tetracarbonylcobaltate catalyzes a facile carbonylative ring opening of epoxides to generate either a polyester such as 314 or a bhydroxy ester such as 315 in good yield (Scheme 104). [348] A 1994 patent reported the dramatic rate enhancement of the [Co 2 (CO) 8 ]-catalyzed carbonylation in the presence of 3-hydroxypyridine (Scheme 105). [349] Careful control of the reaction conditions can allow for the formation of the blactone or polymerization to form polyesters.…”
Section: Lewis Base Catalysis With Cobaltmentioning
confidence: 99%
“…Carbonylation reactions in the absence of hydrogen also found ways into technical application and are nowadays connected to important industrial synthesis like the ''Monsanto process'' for the production of acetic acid from methanol [9] and the ''Reppe carbonylation'' to yield carboxylic acids from olefins and alkynes [10]. Other substrate molecules like epoxides or aziridines were also subjected to carbonylation and hydroformylation conditions during the time of pioneering studies on carbonylative transformations in the 1950s and 1960s [11][12][13]. Little attention was given to these starting materials thereinafter.…”
Section: Introductionmentioning
confidence: 99%
“…As originally reported, (18) this type of reaction was carried out at 130 0 e under 240 bar pressure of carbon monoxide, but with only slight modifications to the catalyst system, the more recent results (Scheme 1.2) were achieved at atmospheric pressure and at temperatures only slightly above ambient. Even after 50 years of continuous development, it is clear that catalytic carbonylation chemistry has not yet reached its full potential.…”
Section: Introductionmentioning
confidence: 67%
“…(62) Early symptoms include headache, giddiness, vomiting or nausea, breathlessness, and weakness of limbs. Subsequently (12)(13)(14)(15)(16)(17)(18) h) there may be severe breathlessness, pain during respiration, dry cough and cyanosis (bluish coloration of face and ears). In the event of an accident the person concerned should be kept warm, put to bed as soon as possible, and then kept lying down.…”
Section: Transition Metal Carbonylsmentioning
confidence: 99%
See 1 more Smart Citation